Gingival Tissue Alterations in 2 Patients with Port Wine Stain - Kocak-Buyukdere Ayse; Guzeldemir Esra (Balkan Stomatological Society, 2014)
Nevus flammeus, which is also known as port-wine stain (PWS), is one of the vascular birthmarks. PWS occurs in 0.3% of the newborns in both genders. It is a capillary vascular malformation, characterized by a pink or red stain and may involve skin, soft tissue and/or bone. There are a very limited number of reports regarding intraoral involvement of PWS. We report 2 female patients with PWS from date of birth. The first patient was an 11-year-old female who applied to our clinics for the treatment of her non-aesthetic and deviated intraoral view and discoloration of her gingiva, and the second patient was a 56-year-old female who applied for the extraction of her wisdom tooth. Extraoral examination in both patients revealed a diffuse PWS on the right side of their face over the cheek, extending from the midline. While the first patient had reddish skin, gingiva on right site her both jaws and lips, the second patient had only her upper jaw and lip. Because of the first patient' age, the treatment postponed to her 20', and the second patient did not accept any treatment. PWS is a rare and non-fatal condition; however, the unique appearance of these patients can lead to psychological problems especially in early ages.